How space can support African civil societies: Security, peace, and development through Efficient Governance Supported by space applications. (June 2022) - Froehlich, Annette; Ringas, Nicolas; Wilson, James
Abstract: This study investigates the vast potential for space-based technologies and applications in supporting governance to strengthen civil society, bolster democratic processes, and allow for socio-economic development throughout Africa. It offers a comprehensive analysis of African governance levels, existing e-governance systems, African challenges relating to e-governance adoption, and how e-governance solutions can assist in realising the continent's development goals. First, the study explores the integral role of good governance in achieving the UN Agenda 2030 Sustainable Development Goals (SDGs) and the AU's Agenda 2063 aspirations. Subsequently, the existing African governance structures established at a continental level are described to provide an overview of the frameworks informing governance within Africa. Specific challenges that need to be overcome to ensure good governance are then addressed and the current governance levels in Africa are evaluated. An assessment of e-government readiness levels both globally and within Africa is offered through an examination of the United Nations E-Government Survey from 2018. Specific barriers to e-government, both abroad and within Africa, are then analysed along with the associated risks relating to e-government systems. It then investigates how digital divides and lack of internet connectivity within Africa can be addressed by new technologies and commitments from both terrestrial and space actors. The opportunities afforded by rapidly growing satellite constellations being deployed to increase connectivity levels and reduce the costs thereof are then analysed in detail and the various planned constellations are assessed on a technical level. Lastly, the potential for Earth Observation and remote sensing data to assist with e-governance activities across sectors including healthcare, education, agriculture, water and sanitation, and emergency responses is investigated. Highlights: Corruption, weak democracies and poor data coverage are impeding African development. Inferior telecommunications infrastructure is preventing e-governance uptake in Africa. Digital divides in Africa include access, affordability, literacy and bandwidth issues. Large constellation LEO-based satellite Internet provides an opportunity for Africa. Increased e-governance uptake will support the socio-economic development of Africa.